The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijerph18052688
|View full text |Cite
|
Sign up to set email alerts
|

Development of Modern Racism Scale in Global Airlines: A Study of Asian Female Flight Attendants

Abstract: Due to the globalization of the airline industry, global airlines are focusing human resource management on diversity strategies and employing flight attendants of various races. Multinational flight attendants have brought many positive results; conversely, discrimination has led to negative phenomena such as racism. Nevertheless, research focusing on global airline racism in tourism studies is unprecedented. Therefore, the purpose of this study is to develop a modern racism scale rating the discrimination pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…According to a Canadian study, white women earned 20% more than racialized women (Tastsoglou & Preston, 2005). Racism and discrimination is undeniably rampant in tourism (Kipp et al, 2021;Yu & Hyun, 2021). Abassah-Oppong and Holmes (2020), in a Canadian study, found that even though 8% of participants reported experiencing workplace discrimination, 27% reported seeing racial discrimination, 27% reported witnessing gender discrimination, and 18% reported witnessing sexual harassment.…”
Section: Reliance On Cheap Labourmentioning
confidence: 99%
“…According to a Canadian study, white women earned 20% more than racialized women (Tastsoglou & Preston, 2005). Racism and discrimination is undeniably rampant in tourism (Kipp et al, 2021;Yu & Hyun, 2021). Abassah-Oppong and Holmes (2020), in a Canadian study, found that even though 8% of participants reported experiencing workplace discrimination, 27% reported seeing racial discrimination, 27% reported witnessing gender discrimination, and 18% reported witnessing sexual harassment.…”
Section: Reliance On Cheap Labourmentioning
confidence: 99%
“…Specifically, it is a business that requires a great deal of labor to produce goods and services. In particular, the cabin crews as front-line employees are mentally and physically engaged, given that passengers spend most of their time on board [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is a business that relies heavily on labor to provide its services. Given that passengers spend the majority of their time on board, the cabin crews in particular are engaged intellectually and physically as front-line workers [2]. In their contact with others, employees must regulate their emotions frequently on the job.…”
Section: Introductionmentioning
confidence: 99%